Transforming learning or creating dependency? Teachers’ perspectives and barriers to AI integration in education - Hardiyanti Pratiwi; Agus Riwanda; Hasruddin Hasruddin; Sujarwo Sujarwo; Amir Syamsudin (Journal of Pedagogical Research)
The emergence of artificial intelligence [AI] in education offers significant potential to enhance personalized learning, feedback, and instructional strategies. However, its effectiveness depends on educators' practices and students' capabilities, especially in rural contexts where the digital divide presents challenges. This qualitative study explores teachers' perceptions of AI integration in education, collecting data from focus group discussions with 127 teachers. AI is viewed as a powerful resource for providing tailored information, enhancing learning depth, and offering immediate assistance to students. However, teachers also highlight the potential for over-dependence on AI, particularly among students with low motivation and literacy levels. In rural, additional challenges include regulations banning smartphone use, which restricts access to AI tools, and weak student motivation due to issues such as misaligned subject placements and assessment criteria that prioritize passing grades over demonstrating actual competencies. The research identifies several significant barriers to AI implementation, including these motivational challenges, limited technological infrastructure, insufficient teacher readiness, and a lack of critical thinking development. Moreover, issues such as low AI literacy and concerns about the ethical implications of AI-generated content are also raised. To effectively integrate AI, the study suggests addressing these barriers through targeted initiatives such as enhancing student motivation, improving digital literacy, and fostering teacher creativity. The findings emphasize the need for a careful and supportive approach to AI integration, ensuring it serves as a tool to enhance, rather than hinder, educational outcomes.